House and Mobility: Portuguese Hindus and Brazilians in Lisbon in face of housing constraints - Cachado, Rita (2019)
This paper explores analytically the relation between experiences of vulnerability, regarding housing processes for people in different kinds of mobility in urban settings. Drawing reflections from two ethnographic contexts in which we have been working, the Hindu-Gujarati and the Brazilian populations in Lisbon, we reflect upon the contours of their experiences, recounting their migration process, and different ways of being under housing vulnerability, as well as their responses to excluding urban politics. The lack of places to inhabit, drives people to different housing solutions, and to a constant mobility, through migration and remigration. These conditions are experienced differently according to the temporality of the mobility paths and projects, and to the type of relation/confrontation with housing policies. Hence, the aim is to understand: what are the strategies of settling within a dynamic of constant mobility? How vulnerability is expressed and qualified in these different settings?